Outcome of Eclamptic Mothers Attending Tertiary Care Centre from Home and those Referred from Primary Heath Care Site: A Comparative study - Pandit, Upendra; Das, Chittaranjan; Banu, Farhat; Ahamad, Shakil (Journal of Lumbini Medical College, 2017)
Introduction: Magnesium sulphate (MgSO4) is an effective and safe drug which stabilizes the patient within few hours of eclampsia and terminates subsequent seizures if it is given on time. The aim of this study was to compare maternal and fetal outcome between a group of eclamptic mothers who came to the tertiary care hospital directly without receiving MgSO4(Group 1) and those referred from primary care centers after receiving loading dose of MgSO4 (Group 2). Methods: This is a retrospective cohort study of eclamptic mothers who were admitted and managed from the period of 1stJanuary 2012 to 31stMarch 2016 at Nepalgunj Medical College Teaching Hospital, Nepal. Socio demographic characters and maternal and fetal outcome was compared between the two groups. Results: Among 92 cases, 57 (62%) were from Group 1 and 35 (38%) were from Group 2. Most of the mothers attended from Banke district (n=52, 56.5%) followed by Bardia district (n=17, 18.5%). Brahmin and Chhetri were 20 (35%) and 10 (29%); Muslim 16 (28%) and four (11%); Janajati from Terai 16 (28%) and eight (23%); Janajati from hilly region four (7%) and five (14%); and Chaudhari one (2%) and eight (23%) in Group 1 and Group 2 respectively. More (n=26, 74%) mothers had baby with good APGAR score in Group 2 than in Group 1 (n=33, 58%). There were 14 (15.2%) still births; nine (16%) in Group 1 and five (14%) in Group 2. Complication rate was observed more in Group 1 (n=16, 28%) than in Group 2 (n=7, 20%) and the most common complication in both groups was wound infection. The mean days of hospital stay was 5.96 (SD=3.32) and 5.91 (SD=3.38) in Group 1 and Group 2 respectively. Conclusion: The group receiving magnesium sulphate in primary care centre have good fetal outcome and less maternal complications compared to those who were admitted directly in tertiary care centre and receive the treatment there. DOI: https://doi.org/10.22502/jlmc.v4i1.79 J. Lumbini. Med. Coll. Vol 4, No 1, Jan-June 2016, Page: 24-27